Early Burn Resuscitation Done By Referring Facilities And Burn Patient’s Survival: A Retrospective Study - Wardhana, Aditya; Handini, Nurliati Sari (Jurnal Plastik Rekonstruksi, 2012)
An acute burn wound is a complex injury, which ideally needs to be handled in a special burn unit. Problems arise when a burn patient come to a facility with no burn unit available. The patient needs to be referred and transferred to the nearest burn unit. The adequacy of burn resuscitation done by the referring facility during the transfer process is important to the patient’s survival. To evaluate this matter, a review of mortality during one-year interval of 2010 is being done in Cipto Mangunkusumo Hospital’s burn unit. We are conducting a retrospective review of all 143 patients with acute burn injuries admitted in 2010 to Cipto Mangunkusumo Hospital’s burn unit, analyzed with bivariate analysis using SPSS. Out of the 143 patients being evaluated, we predict there is a significant level of burn resuscitation inadequacy done by the referring facility which influences the patient’s survival. Survival rates can be improved by providing adequate burn resuscitation during transfer process to the nearest burn unit. It is recommended that efforts on updating the knowledge and awareness of treating burn injury patients is given to nurses and physicians in referring facilities.